Assessment of heavy metals in feed and beef in Bangladesh: A safety issues - MA Hashem; Kamal, MT; Al-Mamun, M; Hossain, MM; Razzaque, MA (Meat Research, 2022)
The study was aimed to assess the heavy metal status in feed and beef produced in Bangladesh. In the study, the quantitative presence/absence of heavy metals in livestock feed ingredients, beef feed and their residues in beef of four district of Bangladesh were investigated.Feeds and meats were analyzed by Atomic Absorption Spectrophotometer (AAS) for heavy metals such as lead (Pb), Chromium (Cr), Cadmium (Cd), Zinc (Zn) and Copper (Cu). Concentration of Zn, Cu, Cr, and Pb in feed ingredients ranged from 0.124 to 1.209 mg/kg, 0 to 0.215 mg/kg, 0.095 to 0.286 mg/kg and 0.164 to 0.301 mg/kg, respectively. In all feed ingredients mean concentration of Zn was higher than other heavy metals. Concentration of Zn, Cu, Cr, and Pb in commercial beef cattlefeed ranged from 0.313 to 1.261 mg/kg, 0.004 to 0.140 mg/kg, 0.223 to 0.459 mg/kg and 0.218 to 0.361 mg/kg, respectively.Pb concentrations were 0.084 ± 0.046, 0.364 ± 0.202, 0.263 ± 0.056, 0.278 ± 0.089, 0.094 ± 0.0466 mg/hg in heart, kidney, liver, lungand muscle, respectively. Cd concentrations were 0.003 ± 0.001, 2.339 ± 0.712, 0.299 ± 0.221, 0.024 ± 0.005, 0.014 ± 0.009 mg/hg in heart, kidney, liver, lung and muscle, respectively. Cr concentrations were 0.555 ± 0.451, 0.164 ± 0.039, 0.199 ± 0.091, 0.512 ± 0.018, 0.232 ± 0.023 mg/hg in heart, kidney, liver, lung and muscle, respectively. Zn concentrations were 6.059 ± 3.362, 9.984 ± 1.358, 14.776 ± 0.816, 1.567 ± 2.625, 15.883 ± 0.438 mg/hg in heart, kidney, liver, lung and muscle, respectively. Cu concentrations were 6.059 ± 3.362, 9.984 ± 1.358, 14.776 ± 0.816, 11.567 ± 2.625, 15.883 ± 0.438 mg/hg in heart, kidney, liver, lung and muscle, respectively which was higher in different organs of beef cattle. The results indicate that the heavy metal residues in feed and feed ingredients were below the maximum residue level (MRL) values, whereas Cu in different organs was slightly higher. Heavy metal residues in feed were in lower concentrations except cadmium, yet below the maximum residue level (MRL). Contaminants existed at different levels in cattle feed and beef of Bangladesh.